Modeling of infrared radiation propagation through thermal insulation surfaces - Levchenko, Larysa; Bolibrukh, Borys; Kovalenko, Oleksandr; Myshchenko, Iryna; Asieieva, Liudmyla (Національний технічний університет "Харківський політехнічний інститут", 2025)
Modeling of the passing heat flow through a layered structure with different thermophysical properties of individual layers was carried out. An air gap of small thickness was assumed between the layers of materials. Changes in the temperature of the outer layer were determined depending on the time of heat passing through the layered structure. The obtained dependences of temperature changes of each layer in time and space. The obtained easyto-use graphical dependencies are suitable for the designing a protective material with the required properties. The temperature gradient between the heat source and the outside space was taken into account. The modeling results were verified using a calibrated infrared radiation detector. It was established that the application of modeling allows to choose the thermophysical characteristics of individual layers the material, which ensure the temperature of the outer layer and is equated to the temperature of the environment. A comparison of the manufactured material with known analogues showed that it has better protective properties with a smaller thickness.

Проведено моделювання проходження теплового потоку крізь шарувату структуру з різними теплофізичними властивостями окремих шарів. Між шарами матеріалів передбачався повітряний проміжок малої товщини. Визначалися зміни температури зовнішнього шару у залежності від часу проходження тепла крізь шарувату структуру. Отримані залежності зміни температури кожного шару у часі і просторі. Отримані зручні у застосуванні графічні залежності, придатні для проєктування захисного матеріалу з потрібними властивостями. Враховувався градієнт температури між джерелом тепла і зовнішнім простором. Проведено верифікацію результатів моделювання з використанням каліброваного детектора інфрачервоного випромінювання. Встановлено, що застосування моделювання дозволяє обрати теплофізичні характеристики окремих шарів матеріалу, які забезпечують температуру зовнішнього шару, яка прирівнюється до температури навколишнього середовища. Порівняння виготовленого матеріалу з відомими аналогами показало, що за меншої товщини він має кращі захисні властивості.
Моделювання поширення інфрачервоного випромінювання крізь теплоізоляційні поверхні
Keywords: modeling; infrared radiation; insulation surfaces; design protective materials; моделювання теплових потоків; інфрачервоне випромінювання; теплоізоляція поверхонь; проєктування захисних матеріалів